Pengaruh Rata Rata Lama Sekolah, Garis Kemiskinan, dan Usia Harapan Hidup terhadap IPM di Provinsi Jawa Tengah - Rodiyah, Anisatu; Destifa Prastiti Kusuma; Nia Bunga Ramadani; Rayya Malik Ibrahim; Rian Ahmadul Huda; Anggi Rahajeng (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of Life Expectancy (LE), Poverty Line, and Average Years of Schooling (AYS) on the Human Development Index (HDI) in Central Java Province. HDI is a crucial indicator used to measure the quality of life through three main dimensions: health, education, and standard of living. The research utilizes 2024 secondary data from all regencies and cities in Central Java, analyzed using multiple linear regression (OLS) with STATA software and spatial regression using Geographically Weighted Regression (GWR) with ArcGIS. The results show that all three independent variables significantly affect HDI. AYS has the most dominant influence, followed by LE and the Poverty Line. Spatial analysis reveals that the impact of each variable varies across regions. Cities such as Salatiga, Boyolali, and Klaten show the highest influence of AYS on HDI, while areas like Kebumen and Tegal show lower impacts. These findings highlight the importance of region-based development policies that consider spatial heterogeneity. This study recommends improving the quality of education and healthcare, along with poverty alleviation efforts, as key strategies to accelerate human development in Central Java Province.